Three-dimensional condylar displacement and remodelling in patients with asymmetrical mandibular prognathism following bilateral sagittal split osteotomy. Issue 4 (April 2022) - Abotaleb, B.M.; Bi, R.; Liu, Y.; Jiang, N.; Telha, W.; Zhu, S.
Abstract: This study aims to assess the postoperative condylar displacement and the long-term condylar remodelling in patients with mandibular prognathism with transverse asymmetry after bilateral sagittal split ramus osteotomy (BSSRO). Forty-one consecutive patients (82 condyles) with a transverse mandibular asymmetry of more than 4 mm without occlusal canting treated by BSSRO were included. The preoperative (T1), immediate postoperative (T2) and long-term follow-up of an average of 16.2 months (T3) spiral computed tomography scans were gathered and processed to measure the condylar displacement and remodelling based on cranial base voxel-based and rigid regional registrations. The statistical analysis revealed that the majority of condyles (T1–T2) were transitionally displaced forwards, downwards and laterally, and were not fully returned to the preoperative position at T3. Condylar lateral displacement was significantly higher on the deviated side (DS) ( P = 0.035). Non-deviated side (NDS) condyles were mainly subjected to upward pitch, medial yaw and medial roll compared with downward pitch, lateral yaw and lateral roll on DS. Condylar remodelling at T3 was observed, with the superior and posterior surfaces commonly subjected to bone resorption, whereas the anterior and medial surfaces were commonly subjected to bone apposition. Condylar volumetric changes were relatively comparable on NDS (3 ± 85.2 mm 3 ) and DS (8.3 ± 111.7 mm 3 ) condyles. Age, amount of preoperative asymmetry and follow-up period were not correlated with the condylar remodelling. Transitional and rotational displacements were to some extent significantly correlated with the condylar remodelling on both sides. Consequently, passive condylar seating without torque might prevent the long-term unfavourable condylar remodelling.